Eliciting a terminology for mammographic calcifications. - Alberdi, E; Taylor, P; Lee, R; Fox, J; Todd-Pokropek, A (2002)
AIM: Two studies were carried out to establish, validate and assess descriptors for use in the differential diagnosis for mammographic calcifications. METHODS: In Study 1, eleven radiologists were asked to 'think out loud' as they interpreted 20 sets of calcifications. Participants used 159 terms to describe calcifications. We used this data to design a scheme with 50 descriptors. In Study 2, ten radiologists used the scheme to describe 40 sets of calcifications. We assessed the capacity of the terms to discriminate between benign and malignant calcifications, testing them against radiologists' assessments of malignancy and follow-up data. RESULTS: All descriptors were used by at least 5 radiologists. Five additional descriptors were required. With some exceptions, properties that discriminated between benign and malignant outcomes were highly correlated with radiologists' assessment of risk. Many descriptors have a fairly low sensitivity but high specificity. CONCLUSIONS: Our data suggest that radiologists consider a wide range of features than is included in existing reporting schemes. Our scheme allows a richer characterization of calcifications, potentially improving the reporting and understanding of these abnormalities.